Análise de ferramentas de mapeamento de dados - Delagustinhi, Pedro Antonio (My University, 2021)
This work aims to analyze and evaluate data mapping tools, in order to identify the tool that most adheres to the ABNT NBR ISO/IEC 27701 standard and the General Law for the Protection of Personal Data. To support this assessment, some concepts about data classification, the General Law for the Protection of Personal Data, norms that manage data privacy (ABNT NBR ISO/IEC 27701) and the norms that govern standards for the evaluation of software quality were studied ( ABNT NBR ISO/IEC 25050 and ABNT NBR ISO/IEC 25030). With the studies, criteria, metrics and test cases were defined for the evaluation of the tools, according to the essential functionalities to comply with the conformity defined by the ABNT NBR ISO/IEC 27701 standard and the General Law for the Protection of Personal Data. The tools for extracting, transforming and loading data Talend Open Studio, Pentaho Kettle and CloverDX were evaluated. Data mapping tools developed to support data protection compliance issues have not been tested as no test versions of them have been made available. Of the tools evaluated, the one with the best result was the Pentaho Kettle. After performing the tests and analyzing them, it is concluded that the data mapping tools used for data extraction, transformation and loading are not the appropriate tools to be used in accordance with the Laws and standards. [resumo fornecido pelo autor]
Este trabalho tem como objetivo analisar e avaliar ferramentas de mapeamento de dados, com o intuito de identificar a ferramenta que mais tem aderências com a norma ABNT NBR ISO/IEC 27701 e a Lei Geral de Proteção de Dados Pessoais. Para fundamentar esta avaliação foram estudados alguns conceitos sobre classificação de dados, a Lei Geral de Proteção de Dados Pessoais, normas que gerem privacidade dos dados (ABNT NBR ISO/IEC 27701) e as normas que regem padrões para a avaliação da qualidade de softwares (ABNT NBR ISO/IEC 25050 e ABNT NBR ISO/IEC 25030). Com os estudos foram definidos critérios, métricas e casos de testes para a avaliação das ferramentas, de acordo com as funcionalidades essenciais para atendimento das conformidades que foram definidas pela norma ABNT NBR ISO/IEC 27701 e a Lei Geral de Proteção de Dados Pessoais. Foram avaliadas as ferramentas de extração, transformação e carregamento de dados Talend Open Studio, Pentaho Kettle e CloverDX. Ferramentas de mapeamento de dados desenvolvidas para apoiar as questões de conformidade de proteção aos dados não foram testadas, pois não são disponibilizadas suas versões de testes. Das ferramentas avaliadas a que obteve melhor resultado foi o Pentaho Kettle. Após realizar os testes e a análise das ferramentas de mapeamento de dados, conclui-se que as ferramentas de mapeamento de dados utilizadas para a extração, transformação e carregamento de dados não são as ferramentas apropriadas para serem utilizadas em conformidade com as Leis e normas. [resumo fornecido pelo autor]
Keywords: Direito à privacidade; Brasil. Lei n. 13.853, de 08 de julho de 2019; Mapeamento digital